Dinâmica sazonal de Amblyomma cajennense sensu stricto em uma área da Amazônia maranhense - ARAÚJO, Flávio Eduardo Saraiva de (2023)
The Amblyomma cajennense sensu stricto tick frequently parasitizes wild and domestic animals, including humans in the Amazon biome. This ectoparasite is the vector of Rickettsia amblyommatis. In this study we evaluated the population dynamics of A. cajennense s.s. in a degraded area of the Amazon biome, and the presence of rickettsiae in this tick population. The study was carried out in a rural area in the municipality of Santa Inês (altitude: 24 meters), in the state of Maranhão. The ticks were collected from the environment over 24 consecutive months, from June 2021 to May 2023. The region is characterized by two warm seasons (~26 º C annually): a rainy season, from november to may, and a dry season, from june to october. We characterized the temporal activity of A. cajennense s.s. in the vegetation, examining the search activity for each life stage (larvae, nymphs, adults [males and females]), in relation to the dry and rainy seasons. The ticks collected in this study were randomly selected and individually tested using a real-time PCR assay that targeted a 147 bp fragment of the rickettsia gltA gene. Overall, 1,843 (62.4%) adults (52.6% females and 47.4% males), 1,110 (37.6%) nymphs and 398 larvais clusters were collected. All adult females, nymphs and larvae were morphologically identified as A. cajennense s.s. Larval activity was observed from april to december, with a peak from june to september (dry season). The peak of nymphs occurred from september to november (transition period between the dry and rainy seasons). Adult ticks were abundant from october to may (spring/summer/early fall). The R. amblyommatis infection rate in A. cajennense s.s. ticks was at least 7% (7/99). Our data suggest a 1-year generation pattern for A. cajennense s.s., with well-defined seasonality of larvae, nymphs and adults in the Amazon biome. Larvae predominate in the dry season, nymphs in the dry/wet transition and adults in the dry season. The presence of R. amblyommatis in adults suggests that animals and humans in the study region are at risk of infection by this rickettsial agent from the spotted fever group.